Stakeholders e o desempenho social corporativo de entidades desportivas do terceiro setor: proposta de mensura????o - Santos, Denis Pereira dos (2016)
Social work sporting institutions of the third sector lacks indicators that can guide decision-making on the part of the managers of these projects. For the measurement of the performance of an institution can use monetary or non-monetary ways. One of the non-monetary forms are the Corporate Social Performance (CSP) or Corporate Social Performance. The concept of Corporate Social Performance (CSP) is related to how an organization reacts against their social demands. This concept is linked to the stakeholder Theory, because the attention to social demands should be analyzed from the perspective of the key stakeholders of the organization. The aim of this study was to evaluate and compare, through the CSP, the social performance of sports institutions of the third sector that have an emphasis in sports performance, sports participation and sports education. As specific objectives, this study sought to identify the stakeholders of the institutions in the view of managers, sorts them according to their degree of legitimacy and urgency power and measure the degree of meeting the demands of the key stakeholders in these sports institutions, featuring so the CSP. For measurement of the CSP was proposed an evaluation tool adapted to sporting institutions of the third sector, and characterize the types of stakeholders linked to each institution and their needs and attendance or not on the part of managers. Empirical research using three selected analysis units for the three possible cases represent third sector linked to the sport, using semi-structured interview, observation and document analysis, in order to provide a triangulation of the data collected. The institutions studied showed levels of CSP relatively close, with emphasis on the institution of sport participation with score of 138 points in the measuring tool of CSP developed in this research. The study concluded that the managers of sporting institutions of the third sector lack indicators for strategic decision-making and that these institutions are more likely to meet the needs of stakeholders, which mainly are related to the form of sport developed within these institutions.